Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1991)
South Africa Debates of Parliament (Hansard).
South Africa Politics and government. Formed by a merger of: Debates of the House of Assembly, Debates of the House of Delegates, and Debates of the House of Representatives. 22 cm.
Keywords: Indexes to Debates; Parliament; Hansard; Third Session; Ninth Parliament; 1 February; 21 June; 1991; Vol. 30; ISBN 0621137464; ISBN 0621137472; JC263111; Index to Speeches; House of Assembly; House of Delegates; House of Representatives